Taḥlīl Qaym Aṡ Ṡaqāfah Al Mujtama’iyyah fī Kitāb “Naḥwu-l-Wāḍih” al-lażī allafahu ‘Alī Al-Jārimīy Wa Musṭafa Amīn Al-Muaṡṡarah Lī Ta’līmi-l-Lugah Al-‘Arabiyyah Li Goiri Nāṭiqīna Bihā - Wahyu Hanafi Putra; Wasilatul Karamah (LISANUDHAD: JURNAL BAHASA, PEMBELAJARAN DAN SASTRA ARAB, 2018)
Taḥlīl Qaym Aṡ  Ṡaqāfah Al Mujtama’iyyah fī Kitāb “Naḥwu-l-Wāḍih” al-lażī allafahu ‘Alī Al-Jārimīy Wa Musṭafa Amīn Al-Muaṡṡarah Lī Ta’līmi-l-Lugah Al-‘Arabiyyah Li Goiri Nāṭiqīna Bihā Wahyu Hanafi, Wasilah KarimahInstitut Sunan Giri Ponorogo, Institut Agama Islam Negeri Pontianakwahyuhanafi89@gmail.com, wasilatul_karamah@ymail.com AbstractThis study aims to analyze the cultural values and its explanations in the book "Nahwu al-Wadhih" by Ali Jarim and Musthofa Amin. The method used in this research is descriptive qualitative. Culture is the ideas, the constitution of life, the beliefs and customs of a society. Levi Strauss stated that there are cultural aspects such as artifact, kinesics, proximics, the visual relationship during kinesthesics, custom in society, the values approaches in society, the orthodox approaches in society and business, society and the arts, seize the times and the ways of doing, sitting and reverence for others, tolerance, praise, endings, cooperation and dignified behavior. All of which are essential for teaching Arabic. The concept of teaching Arabic occurs at the same period as the beginning of the concept of language. Therefore, it was said that language is a fundamental element of culture. We express culture in language and we cannot speak in language which is isolated from culture. Language is the cultural pot and it is the primary means of expression of culture and hence shows us the relationship between culture and language.Keywords; language, culture, Arabic teaching تحليل قيم الثقافة المجتمعية في كتاب "النحو الواضح" الذي ألّفه علي الجاريم ومصطفى أمين المؤثرة لتعليم اللغة العربية لغير الناطقين بهاوحي حنفي ووسيلة الكرامةwahyuhanafi89@gmail.com, wasilatul_karamah@ymail.comجامعة سونان غيري الإسلامية فونوروكو، جامعة إسلامية حكومية بونتياناك الملخص الأهداف في هذا البحث لتحليل قيم الثقافة المجتمعية وبيانها في كتاب النحو الواضح الذي ألفه علي الجارم ومصطفى أمين. وطريقة استقراعيته هي مكتبة البحوث. كما ذكر أن الثقافة هي الأفكار ودستور الحياة والاعتقادات والعادات الموجودة في مجتمع. ورأى ليفي ستراووس (Levi Strauss) بأن نواحي الثقفة وهي المواد الثقافية القديمة (artifact) وتحركات الجوارح (kinesics) والمسافة أثناء الاتصال (proxemics) والعلاقة البصرية أثناء التعامل واللمس (kinesthetics) والعادات والعرف في المجتمع ومناهج القيم السارية في المجتمع والمناهج الاعتقادية في المجتمع وأعمال المجتمع والفنون واغتنام الأوقات وكيفيات القيام والجلوس والوقار على الآخرين والتسامح والمدح والمنهيات والتعاون والسلوك الكريمة. وكلها مؤثرة لتعليم اللغة العربية. ومفهوم تعليم اللغة العربية ببداية مفهوم اللغة. ولذا قيل أن اللغة هي عنصر أساسى من عناصر الثقافة فنحن نعبر عن الثقافة باللغة ولا يمكننا أن نتحدث باللغة بمعزل عن الثقافة. فاللغة وعاء الثقافة و هي الوسيلة الأولى في التعبير عن الثقافة و من هنا تظهر لنا العلاقة بين الثقافة و اللغة.كلمات الرئيسية : اللغة، الثقافة، تعليم اللغة العربية، النحو.